2016
DOI: 10.1016/j.pharep.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of testosterone on cardiometabolic risk factors in atorvastatin-treated men with late-onset hypogonadism

Abstract: Our study may suggest the clinical benefits associated with combination therapy with a statin and testosterone in elderly men with LOH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…Our results were consistent with some previous studies (18)(19)(20)(21)23). A cross-sectional study conducted by Chao (18) indicated a significant negative correlation between SUA and testosterone levels in T2DM males.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results were consistent with some previous studies (18)(19)(20)(21)23). A cross-sectional study conducted by Chao (18) indicated a significant negative correlation between SUA and testosterone levels in T2DM males.…”
Section: Discussionsupporting
confidence: 93%
“…Elevated SUA levels are associated with metabolic syndrome and insulin resistance, both of which increase the risk of low testosterone, so there might be a negative correlation between SUA and testosterone. Some studies have proved SUA is a risk factor for gonadal dysfunction (18), indicating a negative correlation between SUA and testosterone levels (19)(20)(21)(22)(23), which is consistent with our results. However, other studies have come to a different conclusion (24)(25)(26)(27).…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, compared with matched controls, male siblings of women with PCOS were found to have significantly elevated dehydroepiandrosterone-sulfate (DHEA-S) levels [ 9 , 10 , 14 ], as well as lower concentrations of bioavailable testosterone [ 5 ]. Recently, we have observed that exogenous testosterone potentiated lipid-lowering and extra-lipid effects of hypolipidemic agents in subjects with low testosterone levels [ 15 , 16 ]. Therefore, the aim of the current study was to compare the impact of atorvastatin on plasma levels of cardiometabolic risk factors between men whose sisters had either PCOS or were unaffected.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the effect of testosterone manipulation on the SUA levels has been inconsistently reported. Exogenous androgen injection significantly decreased the SUA levels in men with gout or with late-onset hypogonadism [8,9]. However, surgical or medical castration in prostate cancer patients led to a reduction in the SUA level in a small-scale or single-arm study [10,11].…”
Section: Discussionmentioning
confidence: 99%